2018
DOI: 10.1007/s40618-018-0923-z
|View full text |Cite
|
Sign up to set email alerts
|

Clinical features, diagnosis and therapy of pituicytoma: an update

Abstract: Due to both low frequency and the absence of pathognomonic clinical and/or radiological features, formulating a suspicion diagnosis of PT represents a considerable challenge even for experienced professionals. The indication for treatment should be made on an individual basis, but it is inescapable in the presence of a visual field defect. The surgical approach has to be tailored according to the topography of the tumor and preoperative symptoms; the greatest challenges in accomplishing a gross total removal a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 74 publications
0
23
3
Order By: Relevance
“…The number of cases reported in this study is currently the largest number reported by a single center. From the case data we reported, we did not observe a signi cant gender difference, which was slightly different from the larger number of male patients reported in a previous study [15]. Pituicytomas can occur at any age but are more common in middle-aged and elderly individuals [16].…”
Section: Epidemiology and Clinical Characteristicscontrasting
confidence: 81%
“…The number of cases reported in this study is currently the largest number reported by a single center. From the case data we reported, we did not observe a signi cant gender difference, which was slightly different from the larger number of male patients reported in a previous study [15]. Pituicytomas can occur at any age but are more common in middle-aged and elderly individuals [16].…”
Section: Epidemiology and Clinical Characteristicscontrasting
confidence: 81%
“…The number of cases reported in this study is currently the largest number reported by a single center. From the case data we reported, there was no signi cant gender difference, which was slightly different from the larger number of male patients reported in the previous literature [15]. Pituicytomas can occur at any age but are more common in the middle-aged and elderly [16].…”
Section: Epidemiology and Clinical Characteristicscontrasting
confidence: 76%
“…Pituicytomas are rare benign tumors, with only 117 cases in literature reported by a systematic review, 13 of which were treated with EETS. 41,42 Pituicytomas are known to be hypervascular, which can increase operative difficulties because of the risk of bleeding. [43][44][45] Given that more complex endoscopic surgeries have been shown to be associated with meningitis, 7 we speculate that these lesions may be more prone to infection.…”
Section: Tumor Characteristicsmentioning
confidence: 99%